Assessing Large-Scale ERP Implementation Success with a Balanced Scorecard - Rotchanakitumnuai, Siriluck; Speece, Mark; Swierczek, Fredric W (Thammasat Review, 2019)
This study examines large-scale enterprise resource planning (ERP) implementation success factors by looking at their impact on the balanced scorecard (BSC) indicators. Survey research was applied to collect data from large private and public companies (n=275) that have already implemented large-scale ERP (e.g. SAP, ORACLE). ERP Success factors consist of top management support, project management competence, business process engineering, user involvement, knowledge sharing, organization readiness, ERP system quality, and communication with understanding. BSC elements include the four common dimensions of BSC research, organization learning and innovation, internal process improvement, employee satisfaction, and financial benefit to the organization. Results indicated that business process re-engineering has a significant impact on all four BSC dimensions. Other ERP success factors had an impact on some of the BSC factors. However, understanding, user involvement, and organization readiness did not show a significant impact on any of the BSC factors. Top management support showed a negative impact on organization learning and support, contrary to expectations. This paper provides a better understanding of ERP implementation success factors for large-scale ERP, assessing their impacts on the four components of the BSC. The general usefulness of BSC application to ERP is supported, but some inconsistency suggests that there is no one-size-fits-all. Rather, such applications will need to adapt to their context.